Experiential Unity Theory and Model: Treating Trauma in Therapy - Quinn, Alyson (Lexington Books, 2022)
The second edition of Experiential Unity Theory and Model: Treating Trauma in Therapy addresses the impact of trauma prevalent in the field of group therapy and in individual counseling and proposes Experiential Unity theory and model as an effective treatment option. It offers an integrative treatment approach that adheres to the principles of neuroscience and utilizes bottom-up processing, and a right-brain orientation to engage and process trauma. This theory and model has been offered in Individual therapy sessions as a treatment for depression, anxiety, addictions and other trauma- related distress and in Psychiatric Group therapy programs for over fourteen years. It has also been taught in university courses and delivered in workshops internationally, and at the Trauma informed Practice Institute, Vancouver, BC, Canada.